Pemutakhiran Data dan Penyusunan Daftar Pemilih pada Pemilu Tahun 2024 di Kabupaten Subang Perspektif Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum: Data Updates and Compilation of the Voter List for the 2024 General Election in Subang Regency: A Perspective Based on Law No. 7 of 2017 on General Elections - Muhammad Iqbal Ansori; Muhamad Hasan Sebyar (SIYASI: Jurnal Trias Politica, 2024)
The updating of voter data and compilation of voter lists constitutes a crucial stage in democratic election administration to guarantee citizens' constitutional rights. This research aims to analyze the legal framework, implementation mechanism, and effectiveness of voter data updating and voter list compilation in the 2024 General Election in Subang Regency based on the perspective of Law Number 7 of 2017 concerning General Elections. The research employs a normative-juridical method with a descriptive-analytical approach through library research on legislation, official documents of the General Elections Commission (KPU), and academic literature. Research findings indicate that the legal framework for voter list updating has been comprehensively regulated in the 1945 Constitution, Law Number 7 of 2017, and derivative regulations by implementing a de jure system based on domicile according to population documents. However, field implementation faces various problems including duplicate voter data, deceased voters remaining registered, difficulties in data collection in apartments and correctional institutions, and minimal public socialization. The research concludes that synergy between KPU and the Directorate General of Population and Civil Registration is required to ensure voter data validity, strengthening technology-based supervision systems by the Election Supervisory Agency (Bawaslu), and protection of voting rights for citizens in correctional institutions through special mechanisms so that the principle of one man, one vote, one value can be realized in every election administration